2022
DOI: 10.1007/s10113-022-01889-0
|View full text |Cite
|
Sign up to set email alerts
|

Scale-sensitive governance in forest and landscape restoration: a systematic review

Abstract: Building on different bodies of the governance literature, we propose a conceptual framework specifying nine scale-sensitive governance arrangements that aim to (1) create cross-scale fit between the governance and ecological scales, and/or (2) foster cross-level alignment between different governance levels. To understand how scale-sensitive governance has played out in practice, our systematic review builds on 84 peer-reviewed empirical journal articles, which represent 84 cases of forest and landscape resto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 117 publications
0
16
0
Order By: Relevance
“…Yet, when cross-scale and cross-level challenges seem overwhelming, alternatives must be found that offer partial solutions. A nuanced scale-sensitive governance approach is required that takes observed cross-scale and cross-level challenges as a starting point to identify the governance arrangements and strategies that are needed in specific locations and at specific phases of the restoration process, with the aim to create cross-scale fit and cross-level alignment (Wiegant et al, 2022b(Wiegant et al, , 2022a. To make local restoration efforts effective, Ostrom (2009) highlighted that the analysis of interactions across multiple governance levels and across social and ecological systems can enhance efforts to effectively govern natural resources at the local level, and avoid simplistic 'one-size-fits-all' solutions that frequently fail.…”
Section: Reflection On the Cross-scale And Cross-level Challenge Conceptmentioning
confidence: 99%
See 4 more Smart Citations
“…Yet, when cross-scale and cross-level challenges seem overwhelming, alternatives must be found that offer partial solutions. A nuanced scale-sensitive governance approach is required that takes observed cross-scale and cross-level challenges as a starting point to identify the governance arrangements and strategies that are needed in specific locations and at specific phases of the restoration process, with the aim to create cross-scale fit and cross-level alignment (Wiegant et al, 2022b(Wiegant et al, , 2022a. To make local restoration efforts effective, Ostrom (2009) highlighted that the analysis of interactions across multiple governance levels and across social and ecological systems can enhance efforts to effectively govern natural resources at the local level, and avoid simplistic 'one-size-fits-all' solutions that frequently fail.…”
Section: Reflection On the Cross-scale And Cross-level Challenge Conceptmentioning
confidence: 99%
“…In addition, there are various arrangements that can create alignment between governance levels. These are coordination, collaboration, and learning that take place between actors at different governance levels, as well as between bridging organisations and multi-level networks (Wiegant et al, 2022b).…”
Section: Scale-sensitive Governance Arrangements and Strategiesmentioning
confidence: 99%
See 3 more Smart Citations